Thermodynamic Study of Derivatives of PVC Monomer with Nanoparticles of Fullerene, Nanotube and Nanocones at Room Temperature, Using DFT Method - Mohamed A. K. Yousef (International Journal of New Chemistry, 2017)
In this study, the thermodynamic properties of polyvinyl chloride monomer derivatives, PVC with nanoparticles of fullerene, nanotubes and nano cones at room temperature, were studied by DFT method. For this purpose, the materials were first geometric optimized, then the thermodynamic parameters were calculated for all of them. Then, the process of changing the energy-dependent parameters such as specific heat capacity, enthalpy, entropy and Gibbs free energy relative to molecular mass, molecular volume and measured level in this study at a given temperature, were evaluated against each other.